Analisis Beta Saham Harian Terhadap Imbal Saham Harian Sebuah Studi Kasus Saham-Saham LQ45 pada Periode Februari – Juli 2015 - Effendy, Marwan; Pamungkas, Arie Dwi (LPPM Institut Bisnis dan Informatika Kesatuan, 2018)
Go public companies need capital from investors to run the company’s operating activities. The companies can sell its proprietary rights in the form of shares. Currently, shares has been viewed as an interesting instrument of investment by investors to produce quick return (realized return can be seen from historical of closing price) and represented one of the factors that motivated investor for investment. Besides from return, investor also have to calculate risks he would face, which then can be measured by observing the response sensitivitygains of a profits movement toward movement of market gains or called the beta.The purpose of this research is to attaine a beta daily shares movements, the movement of daily shares return, a beta connection daily toward shares return daily and a beta influence daily towards shares return daily. The object of thisresearch are the for LQ45 shares from February – July 2015. Methods of analysis that used in this research are correlation Rank-spearmansn to determine the connection between an independent variable with the dependent variable whether an independent variable and dependent variable associated positive or negative.Simple linear regression method is also used to determine the effect of the independent variable on the dependent variable whether positive or negative effect and to predict the value of the dependent variable when the independent variables increase or decrease with a 5% of significant level. The results concluded that the daily shares beta are significant and positive toward shares return to strength daily but the level n the medium category. This is because most of the factors that affect the return is not incorporated into the research model